SPATIAL DISTRIBUTION OF LANDSLIDE SUSCEPTIBILITY IN NEW ROAD CONSTRUCTION MENGWITANI-SINGARAJA, BALI-INDONESIA: BASED ON GEOSPATIAL DATA - Diara, I Wayan; Suyarto, R.; Saifulloh, Moh (GEOMATE International Society, 2022)
Landslides often occur in the Mengwitani-Singaraja new road construction area. This study aims to analyze the spatial distribution of landslide susceptibility as a basis for disaster mitigation. This study uses a quantitative and descriptive method. Data analysis through scoring technique and thematic map overlay. The parameters needed in this study include the slope, landform, geological structure, rainfall, soil type, and land cover. Spatial analysis was performed using a Geographic Information System (GIS). The study results are categorized into three landslide susceptibility maps, namely high, medium and low. Baturiti and Sukasada sub-districts are areas that have a high level of landslide susceptibility of 15.62. The low landslide susceptibility area is the area that has the highest area, which is 30.38, and the medium landslide susceptibility area is 26.87. Other sites have no susceptibility for landslide susceptibility (27.1 ). High landslide susceptibility because the area is located on volcanic upper slope landforms, volcanic cones, with fractured and sloping geological structures, very steep slopes (> 45), high rainfall (> 2,400 mm/yr.), andosol soil types, as well as land cover with low vegetation density. The occurrence of landslides in the field is spatially dominant on the road section that crosses Candikuning Village to Gitgit Village. Land management is recommended by installing coconut fiber gabions on steep slopes and terraces, plant cultivation according to conservation rules, and the addition of organic matter. © 2022. Int. J. of GEOMATE All rights reserved, including making copies unless permission is obtained from the copyright proprietors.